Human body. (Quezon City : Felta Multi-media, Inc.)
This entertaining approach to the human body engages young, inquisitive learners, while the depth of material gets older students ready for tests. Join Kevin and his friends Marko and Bailey for an enlightening adventure to explore the human body. Clear explanations, beautiful science models, and amusing animations make the DVD perfect for the classroom and home.